Comprehensive phenotyping reveals interactions and functions of Arabidopsis thaliana TCP genes in yield determination. (29th April 2019) - van Es, Sam W.; van der Auweraert, Elwin B.; Silveira, Sylvia R.; Angenent, Gerco C.; van Dijk, Aalt D.J.; Immink, Richard G.H.
Summary: Members of the Arabidopsis thaliana TCP transcription factor (TF) family affect plant growth and development. We systematically quantified the effect of mutagenizing single or multiple TCP TFs and how altered vegetative growth or branching influences final seed yield. We monitored rosette growth over time and branching patterns and seed yield characteristics at the end of the lifecycle. Subsequently, an approach was developed to disentangle vegetative growth and to determine possible effects on seed yield. Analysis of growth parameters showed all investigated tcp mutants to be affected in certain growth aspects compared with wild‐type plants, highlighting the importance of TCP TFs in plant development. Furthermore, we found evidence that all class II TCPs are involved in axillary branch outgrowth, either as inhibitors (BRANCHED‐like genes) or enhancers (JAW‐ and TCP5‐like genes). Comprehensive phenotyping of plants mutant for single or multiple TCP TFs reveals that the proposed opposite functions of class I and class II TCPs in plant growth needs revision and shows complex interactions between closely related TCP genes instead of full genetic redundancy. In various instances, the alterations in vegetative growth or in branching patterns result into negative trade‐off effects on seed yield that were missed in previous studies, showing the importance of comprehensive and quantitative phenotyping. Significance Statement: This study shows the importance of the TCP transcription factor family during Arabidopsis growth and development, coupled to yield and plant architecture. It was found that all class II TCPs are involved in axillary bud outgrowth and that the proposed opposite functioning of class I and class II TCPs requires revision.